Next generation sequencing-based DNA metabarcoding for animal species profiling in fish feed - Khairil Mokhtar, Nur Fadhilah; Imran, Siti Zaharah; Han, Ming Gan; Leong, Mun Chun; Mohd Desa, Mohd Nasir; Raja Nhari, Raja Mohd Hafidz; Mohd Zaki, Nor Nadiha; Yusof, Yus Aniza; Mustafa, Shuhaimi; Mohd Hashim, Amalia (Taylor and Francis, 2022)
The expansion of worldwide aquaculture has been accompanied by extensive growth in the fish feed industry. However, improper labelling of many commercially available fish feeds has raised security and safety concerns over the species’ origin of the ingredients. The inclusion of ruminants-derived ingredients in fish feed is prohibited according to EU legislation while porcine inclusion in fish feed has been a great concern among Muslim farmers. In contrast to the limited species that could be simultaneously determined using multiplex PCR, this study utilised Next Generation Sequencing-based DNA metabarcoding assay to determine the compositional profiles of animal species in fish feed samples in a more holistic manner. In relation to the religious issue associated with porcine-derived ingredients in fish feed, this study firstly aimed to determine the sensitivity of the methods in profiling fish feed adulterated with porcine blood and muscle tissues. Next, 10 commercially available fish feed samples were analysed. As a result, a detection limit of as low as 3% (w/w) porcine muscle and blood in the laboratory-prepared fish feed was obtained. The analysis of 10 commercial fish feeds shows surprising findings: 50% of the feeds contain Sus scrofa and 80% contain Bos taurus, a ruminant. Only one commercial fish feed was found to be solely composed of marine species. This study shows that commercial fish feeds sold in Malaysia contain undesirable animal species, and emphasises the need for accurate and legally enforced labelling of mammalian species in fish feed products.